An Analysis of Persuasive Language Found in TXTURE and Dr. Martens Instagram Advertisement - Mohammad Andre Noer Kholis; Hilda Cahyani; Abdul Muqit (JLT Jurnal Linguistik Terapan, 2025)
This thesis examines the persuasive language techniques used in Instagram advertisements by two leather shoe brands, TXTURE and Dr. Martens, from 2021 to 2023, highlighting how social media has transformed brand communication strategies. Using qualitative content analysis and a survey to assess audience perceptions, the study identifies a range of persuasive appeals—emotional, logical, and social—used in varying styles and frequencies by both brands. TXTURE primarily relies on suggestion (39.28%) and rationalization (33.14%), while Dr. Martens employs a broader array of techniques, with suggestion (51.31%) being most dominant, followed by displacement, identification, and conformity. The findings offer valuable insights into digital marketing strategies, particularly the use of persuasive language to boost audience engagement on social media platforms.